The Kartarpur Pilgrimage Corridor: Negotiating the "Line of Mutual Hatred" - Bochkovskaya, Anna V. (The international journal of religious tourism and pilgrimage, 2021)
After the partition of British India in 1947, many pilgrimage sites important for the Sikhs - followers of a medieval poet-mystic and philosopher Guru Nanak (1469-1539) - turned out to be at different sides of the Indian-Pakistani border. The towns of Nankana Sahib and Kartarpur (Guru Nanak's birthplace, and residence for the last 18 years of his life, respectively) remained within Pakistani territory. Gurdwaras located there represent utmost pilgrimage destinations, the Sikhs’ "Mecca and Medina". Owing to Indian-Pakistani relations that have deteriorated throughout seven decades, pilgrimage to Kartarpur has been extremely difficult for India's citizens. Nevertheless, in the late 1990s, official negotiations were launched concerning the possibility of setting up a visa-free pilgrimage corridor that would allow Indian Sikhs to easily reach the Kartarpur Sahib gurdwara. The potential corridor was perceived by many as a channel for cultural cooperation and the embodiment of a zone of peace at the "line of mutual hatred" - as the India-Pakistan border has often been referred to. Negotiations received a new impetus when the Pakistan Tehrik-e-Insaf (PTI) party headed by Imran Khan came to power in 2018. On November 9, 2019, three days before Guru Nanak's 550th birth anniversary, the Kartarpur corridor was inaugurated by the Prime Ministers of India and Pakistan. This paper discusses the history of and the potential perspectives concerning the Kartarpur pilgrimage corridor drawing upon the concepts of borders as processes, sets of sociocultural practices, symbols, institutions, and networks that permanently adopt new meanings and functions.